Comparative Analysis of the woman and </>женщина Conceptual Representation in English and Russian Languages in the Localization of the Series “The Handmaid's Tale” - N. V. Stepanova; V. N. Matveeva (Дискурс, 2023)
Introduction. The  topic  of  this  study  is  a  cognitive  semantic  analysis  of  the woman/женщина conceptual  representation  in  the  localization of the  series  “The Handmaid's Tale”. Due to the increasing interest in foreign series, the problem of localizing film texts is of particular importance. The relevance of the research topic is determined by the  need  to  study  the  mass  culture  products  from a  linguistic  point  of  view  to  draw conclusions about the most relevant problems of the modern society.Methodology and sources. The  study  aims  to  obtain  objective  conclusions  about  the structure and content of the woman/женщина concepts within a given film discourse. In the course  of  the  research,  such  methods  as  definition  and  lexicographic  analysis  of synonymous  lines,  continuous  sampling  method,  Antconc  machine  analysis,  as  well  as  a cognitive semantic and comparative analysis of the original and localized text were used. The research material is the first season of the TV series “The Handmaid's Tale”, as well as its Russian adaptation. The amount of the analyzed material is 50 000 words.Results and discussion.  The  categorical  structure  of  the  woman concept  consists  of 23 cognitive characteristics, which form 13 classification features. The material under study illustrates the equal level of lexical diversity of the original and localized  texts. The most common  transformation  is  the  replacement  of  a  part  of  speech  since  one-to-one correspondences do not always suit the norms of the translating language. Phraseological units included in the nominative fields of the woman/женщина concepts can be divided into 6 categories and nominate a woman as an object of social and personal relations.Conclusion. The woman/женщина concepts in the framework of a given film discourse are constructed  around  the  idea  of  the  subordinate  position  of  a  woman.  The  predominant component is the interpretative field, which includes emotionally and stylistically charged units.  Thus,  the  evaluative  essence  of  the  concept  under  study  is  doubtless.  Translation transformations enabling a translator to reverbalize the concept with minimal losses are widely used in the localization.